(3gd JLjO GdJaGhV ? (B:s (3CgejJg(B-(3YfGUQg(B-(3eHGOF GdJaGhV(B-(3GSJQGJjLjGJg TNUjI hNUGFU GdeaGhV GdfGLM (B/s - (3EHQGgje, eLOjs ((3GdEScfOQjI, eUQ (B:s (3eGgj ddfTQ hGdJhRjY hNOeGJ GdceHjhJQ,s, 2008)
(3jJMOK gPG GdcJGH Yf GdJaGhV MjK Ef GdJaGhV Yde fSJYedg jhejG aj MjGJfG ShGA OGNd HjhJfG Ch aj MQcI CYeGdfG heTQhYGJfG hdcf gd fLjO gPG Gdaf hfOQc CUhdg hbhGYOg ? heGgj NUGFU GdeaGhV GdfGLM haQjb GdJaGhV ? heG gj GdGSJQGJjLjGJ hCfhGY GdJaGhV GdJj fbGHdgG heG gj YfGUQ GdJaGhV hCgejJg ? cd gPG JLOg HGdTQM GdhGaj OGNd GdcJGH(B.s
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020.s
(3HHdjhLQGajI (B: (3UaMI (B157-158.s
Keywords: (3GdEbfGYs; (3GdeaGhVGJ aj GdCYeGds; (3GdeaGhVGJs -- (3LhGfH faSjIs